The role of human milk and sucrose on cariogenicity of microcosm biofilms - Cácia SIGNORI; Andréia Drawanz HARTWIG; Ivam Freire da SILVA-JÚNIOR; Marcos Britto CORREA; Marina Sousa AZEVEDO; Maximiliano Sérgio CENCI (Brazilian Oral Research, 2018)
Abstract This study investigated the effect of human milk, alone and associated with sucrose, in the cariogenicity of biofilms in a microcosm biofilm model and compared with the cariogenicity of sucrose and bovine milk. Microcosm biofilms were grown in enamel discs in 24-well plates. Six growth conditions were studied: DMM (chemically defined artificial saliva - negative control), DMM with 1% of sucrose (DMM+s) (positive control), human milk with DMM, human milk with DMM+s, bovine milk with DMM, and bovine milk with DMM+s. After 5 days, the outcome variables surface hardness change (%SHC), microbiological composition of biofilms, and pH of supernatant were analyzed. All groups had significantly lower hardness loss compared to the DMM group with 1% of sucrose. Human and bovine milk associated with sucrose showed higher hardness loss. The supernatant pH values after 6 hours of different treatments were similar for the groups sucrose and human milk associated with sucrose (p>0.05). After 18 hours at rest in pure DMM, an increase in the pH of the supernatant was observed. Higher values of total microorganisms count were found for sucrose and bovine milk groups compared to the group supplemented only by DMM. Bovine milk group showed greater amount of total aciduric microorganisms in comparison to human milk group. Within the limits of this study, it can be infered that both human and cow milks have some cariogenic potential, although differing from sucrose in terms of mineral loss.